Reassessing renewable energy - Matthias Weitzel; Alvaro Calzadilla (Kiel Institute for the World Economy (IfW), 2012)
This policy brief presents a long term assessment of low-carbon energies including renewables, nuclear and fossil energy with CCS. It targets the electricity sector from a global to a regional perspective and from centralized to decentralized energy systems. The policy brief aims at finding answers to the following questions: What role can and should renewable energy play in the next decades on the way to a low-carbon energy future? What is the optimal electricity mix (now and in the future)? What are the impli-cations of the optimal mix regarding renewable energy investment and policy? What framework would be needed to enhance international coordination?
Keywords: 330; Energiepolitik; Regenerative Energie; Elektrizitätswirtschaft; Energiemarkt; Welt